1980
DOI: 10.1113/jphysiol.1980.sp013462
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the human jaw stretch reflex increases the resistance of the mandible to small displacements.

Abstract: SUMMARY1. Small 'step' or sinusoidal displacements were imposed on the mandible while human subjects maintained an average biting force of 10 N. Phase-related changes in the force resisting sinusoidal displacement were used to determine the mechanical stiffness of the human mandibular system as a function of the frequency of stretching.2. Jaw-muscle electromyographic (e.m.g.) responses to 'step' stretches were of 8 msec latency and generated a very substantial force response. Jaw-muscle e.m.g. responses having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…In interpreting their experiments on human jaw muscles, Cooker, Larsen & Luschei (1980) used a different method of estimating the non-reflex resistance, which depended partly on the known properties of the jaw muscles, and partly on the response of cat gastrocnemius muscles to sinusoidal stretching.…”
Section: Discussionmentioning
confidence: 99%
“…In interpreting their experiments on human jaw muscles, Cooker, Larsen & Luschei (1980) used a different method of estimating the non-reflex resistance, which depended partly on the known properties of the jaw muscles, and partly on the response of cat gastrocnemius muscles to sinusoidal stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship of force changes to reflex responses Lamarre &Lund (1975) andCooker et al (1980), who were unable to demonstrate a long-latency response in the masseter, concluded that the reflex increase in force evoked by loading the human masseter during an isotonic bite or by stretching the muscle was the result of the monosynaptic response. In the present study, we found that, although jaw-jerk stimuli evoke a high-amplitude monosynaptic reflex in the EMG, little or no force is generated by this electrical response in most subjects.…”
Section: Reflex Pathwaysmentioning
confidence: 99%
“…Godaux & Desmedt, 1975;Murray & Klineberg, 1984). The few studies in which controlled stretch of the jaw-closing muscles has been used to evoke stretch reflexes include those of Marsden, Merton & Morton (1972), Lamarre & Lund (1975) and Cooker, Larson & Luschei (1980) in humans, and Goodwin, Hoffman & Luschei (1978) in monkeys. The characteristic response of most limb muscles to stretch is an initial burst of excitation at monosynaptic latency, followed by a more sustained excitation at longer latency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models provide the most information about a system, and they are the most difficult to obtain. Linear system-identification methods had been used extensively to characterize the dynamics of ankle [14], wrist [15], elbow [16] and jaw [17].…”
Section: Literature Reviewmentioning
confidence: 99%